2015
DOI: 10.3390/ijms160818601
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pharmacogenetics in Hematopoietic Stem Cell Transplantation Outcome in Children

Abstract: Hematopoietic stem cell transplantation (HSCT) is an established therapeutic procedure for several congenital and acquired disorders, both malignant and nonmalignant. Despite the great improvements in HSCT clinical practices over the last few decades, complications, such as graft vs. host disease (GVHD) and sinusoidal obstructive syndrome (SOS), are still largely unpredictable and remain the major causes of morbidity and mortality. Both donor and patient genetic background might influence the success of bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Hematopoietic stem cell transplantation (HSCT) is aimed at restoring the medullary and immunological functions compromised by different clinical situations (Franca et al, 2015; Holtick et al, 2014; Ogonek et al, 2016), such as onco-hematological, autoimmune, metabolic, congenital, hereditary, and some solid tumors (Majhail et al, 2015). According to the World Network for Blood and Bone Marrow Transplantation, there was a progressive increase in the number of transplants performed.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation (HSCT) is aimed at restoring the medullary and immunological functions compromised by different clinical situations (Franca et al, 2015; Holtick et al, 2014; Ogonek et al, 2016), such as onco-hematological, autoimmune, metabolic, congenital, hereditary, and some solid tumors (Majhail et al, 2015). According to the World Network for Blood and Bone Marrow Transplantation, there was a progressive increase in the number of transplants performed.…”
Section: Introductionmentioning
confidence: 99%
“…The target regions for polymorphisms in GSTA1 [G-52A (rs3957356), C-69T (rs3957357), A-513G (rs11964968), T-567G (rs4715332), G-631T (rs4715333), and G-1142C (rs58912740)] and GSTP1 [A313G (rs1695) at codon 105 and C341T (rs1138272) at codon 114] were amplified and sequenced using primers as described previously. 18,19…”
Section: Gstp1 and Gsta1 Polymorphismsmentioning
confidence: 99%
“…methylenetetrahydrofolate reductase and thymidylate synthase genotypes have been associated with aGvHD in recipients receiving methotrexate (164). In 2015, a review article by Franca et al (165) summarized studies on pharmacogenetics variants and GvHD in both adult and pediatric cohorts. Despite the observed genotype effects on pharmacokinetic parameters, the studies found no statistically significant effects on cGvHD.…”
Section: Pharmacogeneticsmentioning
confidence: 99%